The Impact of Work-Related Smartphone Use and Occupational Burnout on Work-Life Conflict : Personal Relationship Satisfaction as Moderator. - Hui Chang, Liew; Sheilla Lim, Omar Lim (2021)
This study examines the association between work-related smartphone use and occupational burnout on work-life conflict, followed by moderating effect of personal relationship satisfaction (PRS). The researchers hypothesize that both work-related smartphone use and occupational burnout as job demands predict an increase in work-life conflict. Meanwhile, PRS as a personal resource is predicted to potentially buffer this stressor-strain model. It is anticipated that at high levels of PRS, the relationship between work-related smartphone uses and occupational burnout on work-life conflict is weaker than at low levels of PRS. 109 Malaysian Administrative and Diplomatic Officers (PTDs) participated in the study. Results indicated that workrelated smartphone use, and occupational burnout significantly increases work-life conflict. Meanwhile, PRS is a significant moderator in buffering the relationship between work-related smartphone use and work-life conflict. By contrast, no support for the hypothesized moderating effect of PRS on the relationship between occupational burnout and work-life conflict was found.